Feeding ecology of common demersal elasmobranch species in the Pacific coast of Costa Rica inferred from stable isotope and stomach content analyses - Espinoza Mendiola, Mario (2015)
Knowledge of the feeding ecology and trophic interactions of marine species is essential to understanding food web dynamics and developing ecosystem-based management approaches. Given that many top predatory fishes have experienced large population declines from coastal ecosystems, it is critical to understand the role of smaller, mesopredators in coastal food webs. This study used stomach content (SCA) and stable isotope analyses (SIA) of muscle tissue (δ13C, δ15N) to examine the feeding ecology of four common demersal elasmobranchs (Mustelus henlei, Raja velezi, Zapteryx xyster and Torpedo peruana) from the Pacific coast of Costa Rica, Central America. Specifically, we investigated: (i) size- and sex-related changes in diet; (ii) dietary changes between seasons; (iii) dietary changes across depth and latitudinal gradients; and (iv) the degree of diet overlap among species. SCA showed that M. henlei, R. velezi and Z. xyster were feeding on a wide range of teleost and decapod species, whereas teleosts dominated the diet of T. peruana. Torpedo peruana had a lower prey diversity and dietary breath than the other species. Interestingly, SIA revealed a significantly larger isotopic niche breath in Z. xyster, indicating that SIA can provide a broader perspective of diet than SCA. Both SCA and SIA showed relatively low dietary overlap among species, except between R. velezi and Z. xyster which have a similar size, mouth morphology and potentially feeding behaviour. Latitude and size were identified as important drivers of the feeding ecology of elasmobranchs; however, their effect varied considerably among species and was often influenced by other factors such as sex and depth. Season had little influence on elasmobranch diet, but our data suggested that isotopic baseline values differ between geographic regions due to differences in local biogeochemical processes and/or prey availability, and possibly in response to seasonal nutrient fluctuations. This may also indicate that some of these elasmobranchs tend to use more localized habitats along the coast. The present study increased our understanding of the feeding ecology of common demersal elasmobranch species. Moreover, trophic information of elasmobranchs provided an important baseline record to understanding how trawling fisheries may impact demersal ecosystems in Costa Rica and the Central American region.